ANALISIS IMPLEMENTASI KEWIRAUSAHAAN SOSIAL DALAM PROGRAM KLINIK SUNGAI UNIVERSITAS CIPUTRA - Maria Satya Rani; Monika Teguh (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2016)
The complex problems in Indonesia require the people initiative to help the government in finding the solution. Thus arise a movement calls social entrepreneurship to identify and solve society problems in large scale. This movement uses the principles of business, but instead of profit oriented it is more social value oriented. Universitas Ciputra Surabaya also performs social entrepreneurship through the